The placenta as a cradle, but not source, of blood? - Julie Y Chen; Kyle M Loh (PLoS Biology)
An important question is whether the placenta is a source of, or merely a niche for, blood-forming hematopoietic stem cells. A recent PLOS Biology study suggests that the placenta does not directly give rise to hematopoietic stem cells.